North Atlantic Catholic Communities in Rome in the 19th Century: Appointment and Ecclesiastical Policies of the First Irish-, American- and Canadian-Born Cardinals (Stato, Chiese e pluralismo confessionale, 2018)
SUMMARY: 1. Introduction - 2. Cardinals and the Internationalization of the Sacred College - 3. The Internationalization of the Catholic Church, the Irish Diaspora and the Transnational Network of North Atlantic Catholic Communities - 4. Appointment and Ecclesiastical Policy of Paul Cullen, the First Irish-Born Cardinal - 5. Appointment and Ecclesiastical Policy of John McCloskey, the First American-Born Cardinal - 6. The First Vatican Council - 7. The 1878 Conclave - 8. Appointment and Ecclesiastical Policy of Elzéar-Alexandre Taschereau, the First Canadian-Born Cardinal - 9. Final Remarks.ABSTRACT: In the second half of the 19th century, when the Roman Curia was still a monopoly held by Italians and few other European nationalities, the first Irish-, American- and Canadian-born cardinals were appointed within the time span of twenty years - respectively in 1866, 1875 and 1886. In the subsequent decades, other Irish-, American- and Canadian-born cardinals were appointed. This development - in a crucial time characterized by the end of the pope’s temporal power - raises important questions: to what extent did the concerned cardinals became ‘Romanized’ and to what extent did they rather contribute to the development of a new vision of their role in the Catholic Church? Also, to what extent did they pursue the interests of their respective national Catholic community, and to what extent did they rather share the same preoccupations and put forward the same demands? In order to answer these questions, this essay will focus on Paul Cullen, John McCloskey and Elzéar-Alexandre Taschereau.
Keywords: Chiesa cattolica